Kiat Belajar Sistem Gerak Karakter Animasi - Erika Dignitya Indraswari (Bina Nusantara University, 2012)
Every animator has a different way of planning to make animated characters motion system. Planning makes animation can be done by making the timing including with the drawing motion pose options on the character, making self-video recording contained own acting choices, and studying references in accordance with the animation that will be created. Creating animated characters requires skills in image selection, acting, and timing. Before going through the process of making animation, an animator must know and understand the characters and situations in a scene. Every movement and action should have a reason to show the personality of the characters in order to complete the story supports. In addition to the nature of the characters, an animator also needs to know the situation in a scene. Many animators use animation principles that have been developed by Walt Disney Studios, USA, to improve their animated creations. Yet, many animators also develop their animated creations using principles that have been developed in Japan. However, the discussion in this paper is the animation using the principles developed in the United States.